Effect of Tip Clearance on the Internal Flow and Hydraulic Performance of a Three-Bladed Inducer. (8th March 2017) - Fu, Yanxia; Yuan, Jianping; Yuan, Shouqi; Pace, Giovanni; d'Agostino, Luca
Abstract : The influence of the tip clearance on the internal flow and hydraulic performances of a 3-bladed inducer, designed at ALTA, Pisa, Italy, are investigated both experimentally and numerically. Two inducer configurations with different blade tip clearances, one about equal to the nominal value and the other 2.5 times larger, are considered to analyze tip leakage effects. The 3D numerical model developed in ANSYS CFX to simulate the flow through the inducer with 2 different clearances under different operating conditions is illustrated. The internal flow fields and hydraulic performance predicted by the CFD model under different operating conditions are compared with the corresponding experimental data obtained from the inducer tests. As expected, both experimental and numerical results indicate that higher pressure rise and hydraulic efficiency are obtained from the inducer configuration with the nominal tip clearance.